Beyond traditional ecological restoration on the Colorado Plateau. Issue 6 (14th September 2018) - Winkler, Daniel E.; Backer, Dana M.; Belnap, Jayne; Bradford, John B.; Butterfield, Bradley J.; Copeland, Stella M.; Duniway, Michael C.; Faist, Akasha M.; Fick, Stephen E.; Jensen, Scott L.; Kramer, Andrea T.; Mann, Rebecca; et al.
Abstract : The Colorado Plateau is one of North America's five major deserts, encompassing 340, 000 km 2 of the western United States, and offering many opportunities for restoration relevant to researchers and land managers in drylands around the globe. The Colorado Plateau is comprised of vast tracts of public land managed by local, state, and federal agencies that oversee a wide range of activities (e.g., mineral and energy extraction, livestock grazing, and recreation). About 75% of the Plateau is managed by federal and tribal agencies and tens of millions of people visit the Plateau's public lands each year. However, even in the face of this diverse use, our knowledge of effective ways to restore Plateau ecosystems remains relatively poor. Further, the multiple agencies on the Plateau have mandates that differ greatly in allowable practices, restoration needs, and desired outcomes. The Colorado Plateau is also expected to undergo ecosystem shifts in the face of climate change, further complicating management decisions and potentially limiting some options while creating others. Here, we explore the current state of Colorado Plateau restoration science and underscore key challenges and opportunities for improving our capacity to maintain the myriad of services provided by these desert ecosystems. We highlight past research efforts and future needs related to restoration concepts, including consideration and design of novel ecosystems, mitigation for and adaptation to climate change, use of genetically diverse seed adapted for current and future conditions, and the value of strong multi‐agency and stakeholder collaborations in restoring systems on the Colorado Plateau and beyond.